Experimental Study on Thermal Conductivity of Sand Solidified by Microbially Induced Calcium Carbonate Precipitation. Issue 5 (September 2019) - Ding, Jinhua; Wang, Zhaoyu; Zhang, Nan; Jiang, Pengming; Peng, Mingxing; Jin, Yong; Li, Qi
Abstract: Soil thermal conductivity is relatively low in low saturation ranges in arid regions, resulting in low heat transfer efficiency of ground source heat pump (GSHP) systems. In this study, thermal conductivity of sand solidified by microbially induced calcium carbonate precipitation (MICP) was measured at different saturation levels. The test results reveal that the thermal conductivity of MICP treated sand increases with the increase in saturation degree (Sr ), and the increasing rate gradually decreases. Use of the MICP technique not only increases the thermal conductivity of sands, but also reduces the influence of saturation degree on sand thermal conductivity when Sr is less than 0.22. This study provides a new research direction for the MICP technique and a technical reference for GSHP applications.